Academic Achievements: Grades versus Duration - Agar Brugiavini; Carlo Carraro; Matija Kovacic (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper investigates the determinants of academic achievements of post-reform undergraduate students of Ca' Foscari University of Venice. Academic achievements are measured with the students' grade point averages and time to graduation. The set of independent variables contains information on students' personal characteristics, prior academic achievements, family background, academic track at university, and several “peer-group” effects. The novelty of this paper is threefold: i) we use a rich data set obtained by matching the University's administrative data records with the data drawn from the AlmaLaurea questionnaires, ii) we pay particular attention to the effects of academic track regularity on students' performance, and iii) we propose a theoretical model of a trade-off between grades and time to graduation, and test empirically its validity by taking into account the problem of reciprocal causation between grades and time to graduation. The model suggests that grades and time to graduation are inversely related. While there is an unambiguous effect of students' ability and financial condition on grades, these effects are less straightforward in the case of time to graduation. The sign and the magnitude of the effects of ability and financial condition on time to graduation depends on students' academic track regularity. Moreover, the relative importance of grades and time to graduation depends, in addition to ability and financial situation, also on the external economic conditions in the labor market. Our empirical exercise confirms the predictions of the model.
Keywords: I21; I23; D91; 330; academic achievements; academic track regularity; trade-off between grades and time to degree; endogeneity; simultaneous equations